PHYSICAL EDUCATION LEARNING IN THE 21st CENTURY - Muhammad Akbar Syafruddin; Haeril Haeril; M Imran Hasanuddin (Perkumpulan Dosen Muda Bengkulu, 2022)
This study uses a qualitative methodology and is descriptive in nature. Papers exploring physical education in the twenty-first century are the data source for this study. The learning process of physical education in the 21st century is different from that of the previous century. This paradigm certainly influences the teaching strategies used to meet the learning needs of students. This reality requires physical education teachers to immediately make adjustments by implementing modern teaching strategies. This modern learning method is expected to provide a better change in education. However, seriousness from the government is needed as a control and evaluation factor in order to achieve goals in learning physical education.